Measuring supply chain smart village headman performance - Thuy To Nguyen Q.L.H.; Nguyen P.T.; Huynh V.D.B.; Vu N.B.; Le L.P.; Vo K.D.; Phan P.T.; Maseleno A.; Hashim W.; Latifah N. (ExcelingTech, 2023)
The supply chain management as the general tool can be used for supporting and delivering the goods to the villages. The village head is the leader of the village government. The tenure of the village head is 6 years, and can be extended for another one term is expected to run the government with a good performance in providing services to the community. So with the proper use of the supply chain the needs of the villages can be provide by the government. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method can help decision making in determining the performance index of the village head. This research is conduct by looking for the performance of positive and negative ideal solutions. Applications with the highest V value will occupy the top size in this system. Then the criteria in determining the performance index of the head of the village are: timeliness, discipline, responsibility, leadership, presence, value. The results of the decision-making system resulted in 6 alternative suggested performance indexes of village heads, with the highest score of Sending Agung Village. ExcelingTech Pub, UK.